Imagining peace(s) in Colombia. Between negotiations, policies, and resisting narratives - Rodríguez Iglesias, Ana Isabel (Araucaria, 2020)
This paper maps and systematizes the different discourses around peace in the public sphere in Colombia during the context of the latest peace negotiations between the government and the guerrilla group FARC-EP. The analysis of the discourses of peace is boiled down to four main approaches: a. Peace is understood as a relational dynamic that allows for the deconstruction of the binary friend-enemy and the recognition of the other; b. peace is seen as a condition that enables security and the deepening of economic development through neoliberal policies; c. peace is re-signified through the signifier ‘territory’, to refer to the need of local involvement to define and implement peace policies in order to take into account the needs from those living and being in the territories; and d. peace is proposed as the consecution of social and environmental justice, accompanied of an alternative development that ensures the autonomy of indigenous, black communities, and peasants to decide how they want to live, how they want to exist. The ultimate goal of this paper is to explore the power-resistance dynamics at play in the re-definition of peace during the window of opportunity that the peace dialogues represented.